(untitled) (Praxis Educativa, 2017)
The concept of Educational Vulnerability refers to those individuals experiencing a number of marked difficulties throughout their school career that prevent them from capitalizing on curriculum and teaching in the classroom. Barriers that may appear to young people on their way through formal education can be of various kinds: emotional, family, interpersonal, related to the teaching and learning or the climate of the educational institution in which are immersed. These conditions usually are accompanied by more complex factors or deep phenomena and, in most cases, lead to failure at school. The aim of this study was to analyze multiple cases of Educational Vulnerability of young people in a technical high school in the state of Yucatan, taking as reference the socio- critical theory.